A Self-Guided Instructional Presentation: Fabrication of a Custom Tray for Fixed Prosthodontics - Charlene Solomon (Association of American Medical Colleges, 2014)
Abstract This publication includes all materials for a self-guided session on the fabrication of a custom tray. This resource includes an Instructor's Guide, a Student Guide, and a 36-slide PowerPoint consisting of color photographs and instructions on the clinical steps required in the fabrication of a custom tray for fixed prosthodontics. The custom trays are made on stone models copied from students' preclinical dentoforms (we use Frasaco™ dentoforms). This self-guided instructional material is designed for dental students and faculty, but is specifically recommended for use in the second-year fixed prosthodontic preclinical setting. This module has been implemented at the University of Manitoba International Degree Dental Program for the (preclinical) review of fixed prosthodontics laboratory techniques with foreign trained dentists. This module provides the student with a learning tool that can encourages independent learning at a self-directed pace.